The Cell: A Molecular Approach - Cooper, Geoffrey M (New York Oxford University Press, 2019)
Even the most experienced instructor can find teaching cell biology daunting, and most cell biology texts are bogged down in detail or background information. Lost in all the details are the more fascinating material and contemporary advances that represent this rapidly moving field. With so much to cover, creating a classroom around active learning may be difficult or nearly impossible. Cooper 8e endeavors to address those issues with succinct writing, incorporation of current research, a test bank that encourages critical thinking, and an active learning framework. With just enough detail for a one-semester, sophomore/junior level course, the Cooper 8e text presents fundamental concepts and current research, including chapters on Genomics and Transcriptional Regulation and Epigenetics, and new in-text boxed features on Molecular Medicine and Key Experiments. Instructors will appreciate updates to the 8e test bank, such as raising the Bloom's level of questions overall, and giving instructors the ability to select questions based on level. Finally, for instructors who want to flip their classrooms or just get students more engaged, Cooper 8e is the only cell biology text that is accompanied by an Active Learning Guide. This chapter-by-chapter playbook shows instructors how to create a dynamic learning environment with in-class exercises, clicker questions, and links to relevant media, animations, testing, and self-quizzing, all aligned with the new in-text learning objectives, wherever appropriate. Cooper 8e provides the right level of detail, student engagement, and instructor support for the modern cell biology classroom.
Keywords: Cytology; Molecular Biology; Cells